Supervisi Akademik Dalam Upaya Peningkatan Motivasi Guru - Muhammad Shofil Himam (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Academic supervision plays a crucial role in enhancing teacher motivation and performance as part of a strategic effort to achieve optimal educational quality. Highly motivated teachers tend to be more active, creative, and responsible in carrying out their teaching duties in the classroom. This study aims to analyze in depth how academic supervision contributes to improving teachers’ work motivation. The method used in this article is a literature review with a descriptive qualitative approach. Data were obtained from various sources such as scholarly journals, reference books, and articles related to supervision and teacher motivation in educational contexts. The findings indicate that academic supervision, when conducted in a structured, scheduled, participatory, and reflective manner, can foster positive professional relationships between supervisors and teachers. Supervision activities that provide opportunities for discussion, constructive feedback, and support in professional development have been proven to boost teacher enthusiasm and self-confidence in delivering effective learning. Therefore, academic supervision functions not only as a monitoring tool but also as a means of continuous coaching and empowerment for teachers.